PENGARUH SOCIAL MEDIA MARKETING TERHADAP NIAT PEMBELIAN ULANG DENGAN BRAND IMAGE DAN BRAND AWARENESS SEBAGAI VARIABEL INTERVENING PADA PRODUK SCARLETT WHITENING - Laili Isrofa; Kussudyarsana Kussudyarsana (LP2M Universitas Bina Bangsa, 2024)
This study aims to analyze the influence of Social Media marketing on Repurchase Intent with Brand Image and Brand Awareness as intervening variables in Scarlett Whitening Products. In this study using 180 respondents. The types of data used are primary and secondary data. Data was collected through an online questionnaire and processed using the Partial Least Square analysis tool with SmartPLS 3.0 software. The results of this study show that: Social Media Marketing has a positive and significant effect on Brand Image. Social Media Marketing has a positive and significant effect on Brand Awareness. Social Media Marketing has a positive and significant effect on Repurchase Intent. Brand Image has a positive and significant effect on Repurchase Intent. Brand Awareness has a positive and significant effect on Repurchase Intent. Brand Image is able to mediate the influence of Social Media Marketing on Repurchase Intent. Brand Awareness is able to mediate the influence of Social Media Marketing on Repurchase Intent